Plants Can Benefit from Herbivory: Stimulatory Effects of Sheep Saliva on Growth of Leymus chinensis - Liu, Jushan; Wang, Ling; Wang, Deli; Bonser, Stephen P.; Sun, Fang; Zhou, Yifa; Gao, Ying; Teng, Xing (PLOS ONE, 2012)
Background Plants and herbivores can evolve beneficial interactions. Growth factors found in animal saliva are probably key factors underlying plant compensatory responses to herbivory. However, there is still a lack of knowledge about how animal saliva interacts with herbivory intensities and how saliva can mobilize photosynthate reserves in damaged plants. Methodology/Principal Findings The study examined compensatory responses to herbivory and sheep saliva addition for the grass species Leymus chinensis in three experiments over three years. The first two experiments were conducted in a factorial design with clipping (four levels in 2006 and five in 2007) and two saliva treatment levels. The third experiment examined the mobilization and allocation of stored carbohydrates following clipping and saliva addition treatments. Animal saliva significantly increased tiller number, number of buds, and biomass, however, there was no effect on height. Furthermore, saliva effects were dependent on herbivory intensities, associated with meristem distribution within perennial grass. Animal saliva was found to accelerate hydrolyzation of fructans and accumulation of glucose and fructose. Conclusions/Significance The results demonstrated a link between saliva and the mobilization of carbohydrates following herbivory, which is an important advance in our understanding of the evolution of plant responses to herbivory. Herbivory intensity dependence of the effects of saliva stresses the significance of optimal grazing management.